Ethnobotanical relevance and conservation of medicinal plants used to treat human diseases in Ifedore, Ondo-State, Nigeria (Asian Journal of Ethnobiology, 2023)
Abstract. Olanipekun MK. 2023. Ethnobotanical relevance and conservation of medicinal plants used to treat human diseases in Ifedore, Ondo-State, Nigeria. Asian J Ethnobiol 6: 7-19. An ethnobotanical study of medicinal plants used by the local people in Ifedore Local Government Area, Nigeria, was conducted to document indigenous knowledge of the importance of medicinal plants. Eighty-four respondents were selected randomly from four villages, and 20 key informants were selected with the help of local administrators, elders, and other community members. Semi-structured interviews, group discussions, and field observation were used for data collection. Descriptive statistics were used for ethnobotanical data analysis. In this study, 98 medicinal plant species belonging to 47 families were collected, identified, and documented. Asteraceae and Solanaceae were the highest families. Most plants were collected from the wild, and herbs were the most growth form. Leaf (63.2%) was the most frequently utilized part. The majority of the identified plants were herbs (55 species, 56%); followed by trees (36 species; 36.7%); climbers (4 species, 4%), and shrubs (3 species, 3%), respectively. The plants were not cultivated (70.4%). The most popular modes of preparation and route of administration were decoction and oral route, respectively. The medicinal plants were reportedly used mostly for treating respiratory tract infections 41 (41.8%). The local people believed that heart disease, liver disease, and urinary tract incontinence had no effective modern medication like herbal mixtures. Ocimum basilicum L. was highly effective in treating diarrhea. Agricultural expansion and building purposes, amongst others, were the most common factors for diminishing the number of medicinal plants. Training and supporting traditional healers with incentives increase their interest in conserving medicinal plants.
Keywords: Conservation, cultivated, ethnobotany, indigenous knowledge, medicinal plant